KETERKAITAN TEMUAN AUDIT DENGAN GOOD CORPORATE GOVERNANCE, ETIKA BISNIS, DAN SISTEM PENGENDALIAN INTERNAL - Hicca Maria Gandi Putri Aruan; Yosi Sihombing; Chintya Hutahaean; Ela Lumban Tungkup; Farel Novsal Simamora; Brian Mendrofa (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the relationship between internal audit findings and Good Corporate Governance (GCG), business ethics, and internal control systems. It specifically examines how internal audit findings reflect corporate compliance with GCG principles, why the root causes of audit findings are often linked to weak organizational business ethics, and how audit recommendations contribute to strengthening internal control systems. This study employs a qualitative literature review approach, examining relevant national SINTA-indexed journal articles and international sources from the past decade, analyzed thematically. The findings show that internal audit findings consistently reflect corporate compliance with the principles of transparency and accountability; the root causes of audit findings are closely related to weak organizational integrity and ethical culture; and audit recommendations contribute significantly to strengthening internal control when consistently followed up by management. This study concludes that internal audit findings, business ethics, and internal control systems operate within a single interrelated ecosystem in realizing Good Corporate Governance, rather than functioning as separate elements